Patients preference for exodontia versus preservation in Malaysia - Razak, I.A.; Jaafar, N.; Jalalludin, R.L.; Esa, R. (1990)
A total of 537 dentate adults from nine randomly selected government dental centers in three states in Malaysia were interviewed to assess their preference for either exodontia or preservation of teeth when they experience toothache, or have carious anterior or posterior teeth. The assumptions tested were i) patients prefer exodontia rather than preservation when they have toothache, and ii) patients are more willing to have posterior teeth extracted than anterior teeth for caries. Both these assumptions were rejected. Even though the majority of the subjects preferred preservation (59) when having toothache, exodontia was the treatment of choice in a large proportion of subjects (41). Significant differences in preference were found among the various ethnic, educational, income, and age groups. However, when ethnicity was held constant, binary regression indicated that the variations observed were determined by education, income, and age groups and not by ethnicity.